2009
DOI: 10.2337/db09-0548
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline Treatment Retards the Onset and Slows the Progression of Diabetes in Human Amylin/Islet Amyloid Polypeptide Transgenic Mice

Abstract: OBJECTIVEAggregation of human amylin/islet amyloid polypeptide (hA/hIAPP) into small soluble β-sheet–containing oligomers is linked to islet β-cell degeneration and the pathogenesis of type 2 diabetes. Here, we used tetracycline, which modifies hA/hIAPP oligomerization, to probe mechanisms whereby hA/hIAPP causes diabetes in hemizygous hA/hIAPP-transgenic mice.RESEARCH DESIGN AND METHODSWe chronically treated hemizygous hA/hIAPP transgenic mice with oral tetracycline to determine its effects on rates of diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
61
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 38 publications
5
61
0
Order By: Relevance
“…Human amylin's physiological conformation is one of random coil, but it undergoes rapid conformational change into β-conformers when placed in physiological solutions [35]. Based on the available evidence, many workers have concluded that small oligomers formed by aggregated human amylin [36,37] are probably the species that could ultimately cause diabetes [38,39]. Others, among them Zraika and colleagues, believe that the cytotoxicity of larger amyloid fibrils must be considered [11,15], as indeed it must.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Human amylin's physiological conformation is one of random coil, but it undergoes rapid conformational change into β-conformers when placed in physiological solutions [35]. Based on the available evidence, many workers have concluded that small oligomers formed by aggregated human amylin [36,37] are probably the species that could ultimately cause diabetes [38,39]. Others, among them Zraika and colleagues, believe that the cytotoxicity of larger amyloid fibrils must be considered [11,15], as indeed it must.…”
mentioning
confidence: 99%
“…Zraika et al have argued that mature amyloid fibrils, rather than small, soluble cytotoxic oligomers [37][38][39]43], could play the main role in beta cell degeneration and diabetes causation. As noted, they have pointed to the numerous weaknesses and shortcomings of the currently available evidence, and in so doing have indicated further lines of investigation that might improve our understanding.…”
mentioning
confidence: 99%
See 3 more Smart Citations